Dual Inhibition of AChE and BChE with the C-5 Substituted Derivative of Meldrum’s Acid: Synthesis, Structure Elucidation, and Molecular Docking Studies - Haroon Mehfooz; Aamer Saeed; Anamika Sharma; Fernando Albericio; Fayaz Ali Larik; Farukh Jabeen; Pervaiz Ali Channar; Ulrich Flörke (Crystals, 2017)
Alzheimer’s disease (AD) lies in the category of those diseases which are still posing challenges to medicinal chemists, and the search for super-effective drugs for the treatment of AD is a work in progress. The inhibition of cholinesterase is considered a viable strategy to enhance the level of acetylcholine in the brain. The C-5 substituted derivative of Meldrum’s acid was synthesized and screened against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzyme inhibition activity. The simple and unique structure of synthesized derivative 3 was found to be good for the dual inhibition of both enzymes (AChE and BChE). 2,2-Dimethyl-5-(([2-(trifluoromethyl) phenyl]amino)methylidene)-1,3-dioxane-4,6-dione (3) showed significant inhibition against AChE, with an IC50 value of 1.13 ± 0.03 µ M (Standard Neostigmine 22.2 ± 3.2 µM), and moderate inhibition against BChE, with an IC50 value of 2.12 ± 1.22 µM (Standard Neostigmine 49.6 ± 6.11 µM). The structural insights reveal that compound 3 possesses intriguing reactive groups, which can potentially evoke the non-covalent interactions and possibly assist by binding in the active site of the target protein. Docking simulations revealed that the compound 3 showed binding inside the active site gorges of both AChE and BChE. An excellent agreement was obtained, as the best docked poses showed important binding features mostly based on interactions due to oxygen atoms and the aromatic moieties of the compound. The docking computations coupled with the experimental findings ascertained that the compound 3 can serve as a scaffold for the dual inhibitors of the human acetylcholine esterases.